New species of Soa Enderlein, 1904 (Psocodea: ‘Psocoptera’: Lepidopsocidae) from the Western Ghats of India - Ramesh, Gurusamy; Babu, Rajappa; Subramanian, Kumarapuram A. (Zootaxa, 2020)
Soa papanasam sp. nov. is described and illustrated based on both sexes from Kalakkad Mundanthurai Tiger Reserve and Meghamalai Wildlife Sanctuary, Tamil Nadu, India. It differs from all other known species of Soa, by hindwing vein R1 originating proximal to vein M1 and distal to M2. This is the first species of the genus Soa described from India.